Fetuin A in nonalcoholic fatty liver disease: in vivo and in vitro studies - Haukeland, John Willy; Dahl, Tuva B; Yndestad, Arne; Gladhaug, Ivar P; Løberg, Else Marit; Haaland, Terese; Konopski, Zbigniew; Wium, Cecilie; Aasheim, Erlend T; Johansen, Odd Erik; Aukrust, Pål; Halvorsen, Bente; et al. (European journal of endocrinology, 2012)
ObjectiveFetuin A has been associated with insulin resistance and the metabolic syndrome. We therefore explored the role of fetuin A in nonalcoholic fatty liver disease (NAFLD).DesignCross-sectional and intervention studies.MethodsWe included 111 subjects with histologically proven NAFLD of whom 44 participated in a randomized, controlled trial with metformin. One hundred and thirty-one healthy subjects and 13 subjects undergoing hepatic surgery for metastatic cancer served as controls. Main outcome variables were circulating levels of fetuin A according to the presence of NAFLD, hepatic gene expression of fetuin A and key enzymes in glucose and lipid metabolism, and the effect of metformin on fetuin A levels in vivo and in vitro (HepG2 cells).ResultsFetuin A levels were significantly higher in NAFLD patients compared with controls (324±98 vs 225±75 mg/l, P<0.001). NAFLD was a significant predictor of elevated fetuin A levels (β=174 (95% confidence interval: 110–234)) independent of body mass index, age, sex, fasting glucose, and triglycerides. Hepatic fetuin A mRNA levels correlated significantly with hepatic mRNA levels of key enzymes in lipid (sterol regulatory element-binding protein 1c, carnitine palmitoyltransferase 1) and glucose (phosphoenol pyruvate kinase 1, glucose-6-phosphatase) metabolism. Plasma fetuin A levels decreased significantly after metformin treatment compared with placebo (−40±47 vs 15±82 mg/l, P=0.008). Metformin induced a dose-dependent decrease in fetuin A secretion in vitro.ConclusionsFetuin A levels were elevated in NAFLD. Hepatic expression of fetuin A correlated with key enzymes in glucose and lipid metabolism. Metformin decreased fetuin A levels in vitro.